ANALYSIS ACCOUNTABILITY OF CASH WAQF MANAGEMENT AT AL AZHAR INDONESIA - Rahmi, Asri Noer; Sevriana, Lufthia; Rachman, Muhamad Emil; Luminaries, Rayan Asa (AGROTEKSOS; Vol 36 No 1 (2026): Jurnal Agroteksos April 2026, 2026)
This research aims to analyze the accountability management of cash waqf  at Al Azhar Indonesia, with a focus on the management of waqf funds. Cash Waqf has become a important source of funding in the administration of cash waqf at Al Azhar. The research method employed includes document analysis and interviews with relevant parties. A brief overview of cash waqf collection management and analysis is presented. Firstly, it outlines the strategies for collecting cash waqf funds, including marketing, communication, and approaches used to encourage community participation in cash waqf. Transparency and accountability are also highly important in cash waqf collection management, including clear reporting on the utilization of waqf funds to donors or waqifs. However, this research also identifies several challenges, such as expanding the donor base, enhancing public understanding of cash waqf, and efforts to maintain waqf funds to ensure sustainability. Therefore, this research provides recommendations to enhance cash waqf collection management, including more effective communication strategies and the development of educational programs on cash waqf. This research is expected to provide valuable insights for practitioners and stakeholders in their efforts to improve cash waqf collection at Al Azhar Waqf and other waqf institutions, thereby supporting social development and the sustainability of waqf funding sources.